2019
DOI: 10.1155/2019/9362492
|View full text |Cite
|
Sign up to set email alerts
|

Markov Chain Modeling of HIV, Tuberculosis, and Hepatitis B Transmission in Ghana

Abstract: Several mathematical and standard epidemiological models have been proposed in studying infectious disease dynamics. These models help to understand the spread of disease infections. However, most of these models are not able to estimate other relevant disease metrics such as probability of first infection and recovery as well as the expected time to infection and recovery for both susceptible and infected individuals. That is, most of the standard epidemiological models used in estimating transition probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
(7 reference statements)
2
6
0
Order By: Relevance
“…In this study Markov chain model showed that both rate of infection and severity were relatively low in all the three classifications. The findings relate with Twumasi et al (2019) where similar outcome, was obtained but with different disease scope namely, HIV, Hepatitis B (HBV) and tuberculosis TB). These diseases are classified as infectious diseases.…”
Section: Discussionsupporting
confidence: 75%
“…In this study Markov chain model showed that both rate of infection and severity were relatively low in all the three classifications. The findings relate with Twumasi et al (2019) where similar outcome, was obtained but with different disease scope namely, HIV, Hepatitis B (HBV) and tuberculosis TB). These diseases are classified as infectious diseases.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, estimates of the epidemic thresholds (R 0 � 0.53 < 1, ρ � − 0.073 < 0, and q c � − 0.87 < 0) from bootstrap, jackknife, and Latin Hypercube sampling schemes for the entire region suggested that there may not be tuberculosis outbreak in the Ashanti Region since the probability of TB extinction was unity within the region as a whole; hence, the disease-free equilibrium point will be stable for the entire Ashanti Region. A similar result was found by Twumasi et al where they discovered with a certain probability that TB-infected individuals can recover in the region via a discrete-time Markov model [37]. Nonetheless, approximately 12% and 14% of the study population in Obuasi Municipal and Amansie West district, respectively, need TB immunization to control the spread of the disease.…”
Section: Type Of Modelsupporting
confidence: 84%
“…Markov chain models are able to estimate relevant disease metrics such as probability of first infection and recovery as well as the expected time to infection and recovery for both susceptible and infected individuals. These models can generalize the transition estimates of disease outcomes at discrete time steps for future predictions (Twumasi et al, 2019).…”
Section: Our Model Vs Markov Chain and Cellular Automata Modelsmentioning
confidence: 99%